2001
DOI: 10.1091/mbc.12.3.725
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism in the Sequential Control of Cell Morphology and S Phase Entry by Epidermal Growth Factor Involves Distinct MEK/ERK Activations

Abstract: Cell shape plays a role in cell growth, differentiation, and death. Herein, we used the hepatocyte, a normal, highly differentiated cell characterized by a long G1 phase, to understand the mechanisms that link cell shape to growth. First, evidence was provided that the mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) cascade is a key transduction pathway controlling the hepatocyte morphology. MEK2/ERK2 activation in early G1 phase did not lead to cell proliferation but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 58 publications
2
86
2
Order By: Relevance
“…No significant differences could be noticed between the two chemically modified sequences and no changes with all control mutated sequences. In parallel, we looked at cell cycle markers expressions of cyclin D1 (Figure 5a) and Cdk1 (Figure 5b), two markers which are expressed, respectively, at late G 1 and S phase in normal hepatocytes and in HCC (Albrecht et al, 1993(Albrecht et al, , 1995Ito et al, 1998;Rescan et al, 2001). Our results showed that cyclin D1 inhibition was partially inhibited in transfected cells.…”
Section: Erk2 Targeting Inhibits Tumor Growthmentioning
confidence: 77%
See 2 more Smart Citations
“…No significant differences could be noticed between the two chemically modified sequences and no changes with all control mutated sequences. In parallel, we looked at cell cycle markers expressions of cyclin D1 (Figure 5a) and Cdk1 (Figure 5b), two markers which are expressed, respectively, at late G 1 and S phase in normal hepatocytes and in HCC (Albrecht et al, 1993(Albrecht et al, , 1995Ito et al, 1998;Rescan et al, 2001). Our results showed that cyclin D1 inhibition was partially inhibited in transfected cells.…”
Section: Erk2 Targeting Inhibits Tumor Growthmentioning
confidence: 77%
“…In primary culture of normal hepatocytes, expression of Cdk1, one marker of G 1 /S phase transition, is regulated by the MEK/ERK pathway (Albrecht et al, 1993;Rescan et al, 2001;Huynh et al, 2003). Therefore, we looked at the regulation of this protein in transformed FAO cells and showed that Cdk1 expression was significantly blocked when cells were treated with U0126 ( Figure 1b).…”
Section: Proliferation Of Hepatocarcinoma Cells Is Mediated By the Mementioning
confidence: 99%
See 1 more Smart Citation
“…TGFa and EGF stimulate hepatocellular DNA synthesis and act as potent mitogens for hepatocytes (Mead and Fausto, 1989;Rescan et al, 2001). Overexpression of TGFa is frequently observed in human HCCs and patients suffering from HCC may have elevated urinary TGFa levels (Yeh et al, 1987;Chuang et al, 1991).…”
Section: Transforming Growth Factor A/epidermal Growth Factor Signalimentioning
confidence: 99%
“…EGF and TGFa are potent mitogens for hepatocytes (Wang et al, 1999;Rescan et al, 2001). Signalling of these mitogens is through binding to members of the EGF-receptor family.…”
Section: Introductionmentioning
confidence: 99%